Color Scheming - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet provides tips for homeowners determining a fresh color scheme for their home exterior. Suggests noting the colors of the roof and neighboring home to avoid clashing colors, and describes the findings of a survey of exterior decoration trends. Includes small stylized illustrations throughout and decorated covers. The National Paint, Oil and Varnish Association, Inc., formed in 1933, was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Exterior walls--Design and construction; Paint materials; House painting; Oilseeds; Varnish and varnishing; Varnish industry; Paint industry and trade; Advertising--Paint